Physical oceanography during SONNE cruise SO289 (Titanium CTD 1 m resolution) - Zvi Steiner; Gerd Krahmann; Eric Pieter Achterberg (PANGAEA, 2023)
During RV Sonne cruise SO289 from Valparaiso, Chile to Nouméa, New Caledonia (GEOTRACES GP21 transect) during February – April 2022 two SeaBird SBE911Plus CTD were deployed at 44 different stations. One CTD was mounted on a stainless-steel rosette and was connected to the following sensors: Pressure (Digiquartz with TC), two temperature sensors (ITS90 °C), two conductivity sensors, oxygen (SBE43), PAR (Biospherical Licor Chelsea sensor), fluorometer (Wet Labs ECO-AFL/FL), turbidity (Wet Labs ECO-NTU) and an altimeter. The second CTD was mounted on a titanium rosette used for trace metal clean collection of water samples, and was connected to the following sensors: Pressure (Digiquartz with TC), two temperature sensors (ITS90 °C), two conductivity sensors, two oxygen sensors (SBE43), transmissometer (Wet Labs C-Star), turbidity (OBS Seapoint) and an altimeter. The oxygen and salinity data were calibrated against discrete water samples.